The Development of E-commerce in the Context of the Digitalization of the Economy - Verbivska Liudmyla, Liudmyla (Review of Economics and Finance, 2023)
The development of e-commerce is an integral part of the modern market for goods and services, and against the background of the digitalization of companies, the introduction of sales of goods and promotion of services through online channels creates additional conditions for the development of new markets and strengthening its position in existing ones. After the COVID-19 pandemic, the promotion of products and services through the Internet became an opportunity to maintain an audience and ensure stable sales even in the face of a lockdown. According to many scholars, partly due to e-commerce, markets were able to recover from the quarantine restrictions fairly quickly. Given the importance of the problem in question, the purpose of this article is to define the role of ecommerce in the process of digitalization of business based on the analysis of its development trends. The study is built in the context of consideration of the peculiarities of e-commerce organization for both the B2B and B2C segments, focusing on determining the differences between these two types and the specifics of the use of e-commerce for each of these areas. The study also realized an analysis of statistical material which proves the extreme importance and steady growth of sales of goods and services with the use of electronic commerce. In addition, it is found that the main players in the market of digital sales of goods and services are China and the United States, as these are the countries where powerful sales platforms are registered and operate, viz: AliExpress and Amazon. As a result of the systematization of scientists' views on the prospects of e-commerce development, promising directions were formed and trends of development of this sphere in Ukraine in the period of post-war recovery were outlined, the advantages received by manufacturers and trade intermediaries in case of using e-commerce were concretized.
Liudmyla Verbivska, Nataliia Sarai, Maryna Ivashchenko, Nataliia Havrylenko, and Olha Kuznietsova. The Development of E-commerce in the Context of the Digitalization of the Economy. Review of Economics and Finance. vol.21.2023.
Keywords: E-commerce, Online sales, Digitalization of the economy, Social networks, Online platforms.